2020
DOI: 10.3390/nu12051280
|View full text |Cite
|
Sign up to set email alerts
|

Grape Polyphenols Ameliorate Muscle Decline Reducing Oxidative Stress and Oxidative Damage in Aged Rats

Abstract: A large number of studies have demonstrated the implication of oxidative stress (OxS) in the pathogenesis of ageing-related muscle decline and atrophy. The key mechanism is related to the OxS-induced production of free radicals, with the consequent increase in oxidative damage, resulting in affected muscle quality and strength. The present study aimed to evaluate the efficacy of a grape polyphenol-based nutraceutical formulation (Taurisolo®) in reducing the OxS in muscle of aged rats. A group of 16 aged (20 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 73 publications
0
17
0
1
Order By: Relevance
“…As the LC-MS analysis shown, polyphenols are main bioactive compounds of R. sacra too. Moreover, Capó and his colleagues found that polyphenolic extract ameliorate muscle decline in by reducing oxidative stress and oxidative damage (Annunziata et al, 2020). Thus, polyphenols might be responsible for the biological effects of R. sacra in the study and could be another potential treatment for HFD-induced muscle atrophy, but more data is needed.…”
Section: Discussionmentioning
confidence: 89%
“…As the LC-MS analysis shown, polyphenols are main bioactive compounds of R. sacra too. Moreover, Capó and his colleagues found that polyphenolic extract ameliorate muscle decline in by reducing oxidative stress and oxidative damage (Annunziata et al, 2020). Thus, polyphenols might be responsible for the biological effects of R. sacra in the study and could be another potential treatment for HFD-induced muscle atrophy, but more data is needed.…”
Section: Discussionmentioning
confidence: 89%
“…Concretely, the anti-oxidative effects may be due to the polyphenol components found in the mixture [ 29 ]. Other authors have reported the beneficial effects of polyphenols in reducing oxidative stress and improving aged-muscle performance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some nutraceuticals based on polyphenols have already showed efficacy in reducing the oxidized lowdensity lipoprotein levels and trimethylamine N-oxide (TMAO is a recognized biomarker of increased cardiovascular risk) serum levels in overweight/obese adults [78] and the gut microbiota remodeling [79]. At the same time, these products have also demonstrated a reduced OS and the oxidative damage at muscular level and improved the muscle performance but in aged rats [80]. Table 2 provides a summary of the different polyphenol families found in grapes.…”
Section: Polyphenols: a Natural Source Of Antioxidantsmentioning
confidence: 99%